Arbuscular mycorrhizal colonization of tomato by Gigaspora and Glomus species in the presence of root flavonoids - Scervino, Jose Martin (2005)
The effect of flavonoids isolated from arbuscular mycorrhizal (AM) colonized and noncolonized clover roots on the number of entry points and percentage of root colonization of tomato (Lycopersicum esculentum L.) by Gigaspora rosea, Gi margarita, Glomus mosseae and G. intrarradices symbionts was determined. With fungi of both genera, a correlation between the number of entry points and the percentage of root colonization was found in the presence of some of the tested flavonoids. The flavonoids acacetin and rhamnetin, present in AM clover roots, inhibited the formation of AM penetration structures and the AM colonization of tomato roots, whereas the flavonoid 5,6,7,8,9-hydroxy chalcone, which could not be detected in AM clover root, inhibited both parameters. The flavonoid quercetin, which was present in AM clover roots, stimulated the penetration and root colonization of tomato by Gigaspora. However, the flavonoids 5,6,7,8-hydroxy-4′-methoxy flavone and 3,5,6,7,4′-hydroxy flavone, which was not found in AM clover root, increased the number of entry points and the AM colonization of tomato roots by Gigaspora. These results indicated that flavonoids could be implicated in the process of regulation of AM colonization in plant root, but its role is highly complex and depend not only on flavonoids, but also on AM fungal genus or even species.